The effect of atenolol and combination of atenolol and thiazide diuretic on the lipid profile in hypertensive patients - Jawna Khalid Mamdoh; Faris A. Ahmed (University of Mosul, 2005)
Objectives: To assess the effect of atenolol and combination of atenolol and diuresam (hydrochlorthiazide, 25 mg and amiloride, 5 mg) on the lipid profile including serum total cholesterol, triglyceride, very low density lipoprotein-cholesterol (VLDL-C), low density lipoprotein cholesterol (LDL-C) and high density lipoprotein-cholesterol (HDL-C) in hypertensive patients. Design: Case-control study. Setting: The study was conducted in Outpatient department of Ibn-Senna Hospital in Mosul, during the period from December 2003 to July 2004. Participants: Fifty hypertensive patients under atenolol therapy (100 mg/day) and 40 hypertensive patients under combination therapy of atenolol (100 mg/day) and diuresam (one tablet every other day). In addition to that, 50 stage 1 hypertensive patients without treatment served as a control group. Mean outcome measures: lipid profile in the treated hypertensive patients were compared with those measurements in the control group by using Duncan test. Results: In the hypertensive patients treated with atenolol, serum total cholesterol, triglyceride, VLDL-C and LDL-C were significantly higher (P